Carole Pateman: o problema da subordinação presente nos contratos - Salles, Rafaela Ortiz de (2024)
The present research consists in the reading of “O contrato sexual” by Carole Pateman, in the attempt to identify a few arguments presented by the author to uncover the patriarchal assumptions underlying the modern political theories. The problem in which Pateman shows interest is in how classical theories of the contract appear daily in the world’s new reformulations, where the sexual difference is a political difference. However, for this opportunity, we are focusing on the concept of modern civilian subordination, as well as other problems which unfold from this concept. Pateman highlights that subordination is intrinsic to the original contract, but this aspect has been neglected for a long time. From this concept of modern civilian subordination which the author presents us, we are going to problematize the concept of self-ownership, seeking to present such concept, being accepted as the standard terminology in contemporary political theoretical discussions it ended up excluding the debates about the concept of sovereignty, which implies directly in silencing the problematics that are present in these concepts of alienability, inalienability and contract, also including the concept of property in the person who is implied in these discussions, because the way that the self-ownership is interpreted is also related to the interpretation of autonomy and rights. Therefore, in this study we are proposing to carry out a theoretical movement, keeping in mind the unfolding of the conceptual knot presented so far, such as the concepts of self-ownership, property in the person, contract and subordination, as well as the intrinsic relation to the notion of alienability and inalienability. In addition, it will be sought to question along with the author who the individuals are – owners of themselves – who populate the pages of the contractual theorists. Even though the modern age’s individual is lined up with the ideals of equality, universality and neutrality, it is still an owner and a masculine individual. In the face of that, we will be looking into in which way, even when they do not say it explicitly, the contractualists provided arguments to the women’s natural exclusion from the civilian and public space, designating to them a private and natural space. Although we might refer to the contractualist tradition as a set of theories that narrates the genesis of the civilian society and the political right, which are similar for many aspects, there are still a few elements which are singular to each of the authors. For that reason, to our own purpose, Jean-Jacques Rousseau was chosen here as an emblematic example of the contractualist tradition, for it provides us, expressively, the way that the dichotomic thought’s formation works which opposes to the reason and the desire, natural and civil and, consequently, public and private. For the problematics which will be developed during this research, the hypothesis is defined, whatever it is, in which way Rousseau consolidated the division of public/private through the imposition of gender roles. Thus, the book we will be seeking theoretical support is “Emílio ou da Educação”. Following this path, it can be thought about the rigid division imposed between the public sphere and the private sphere, and how such division legitimated the allocation of individuals in distinct ways and spheres of life based on sexual differences.